2019
DOI: 10.1093/nar/gkz1156
|View full text |Cite
|
Sign up to set email alerts
|

A versatile cis-acting element reporter system to study the function, maturation and stability of ribosomal RNA mutants in archaea

Abstract: General molecular principles of ribosome biogenesis have been well explored in bacteria and eukaryotes. Collectively, these studies have revealed important functional differences and few similarities between these processes. Phylogenetic studies suggest that the information processing machineries from archaea and eukaryotes are evolutionary more closely related than their bacterial counterparts. These observations raise the question of how ribosome synthesis in archaea may proceed in vivo. In this study, we de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 108 publications
9
40
0
Order By: Relevance
“…Moreover, we have hypothesized that ligation of the 16S rRNA leader/trailer resulting from the 16S rRNA bulge-helix-bulge maturation process generates a putative new pre-rRNA intermediate which we could observe for the first time in Pyrococcus using native RNA sequencing. In addition, the presence of intermediates (1) and (3) support the idea that the maturation of the co-transcribed internal tRNA is inefficient or inhibited and may preferentially occur after processing of the 16S and 23S rRNA bulge-helix-bulge [suggested in 76,78 ].…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Moreover, we have hypothesized that ligation of the 16S rRNA leader/trailer resulting from the 16S rRNA bulge-helix-bulge maturation process generates a putative new pre-rRNA intermediate which we could observe for the first time in Pyrococcus using native RNA sequencing. In addition, the presence of intermediates (1) and (3) support the idea that the maturation of the co-transcribed internal tRNA is inefficient or inhibited and may preferentially occur after processing of the 16S and 23S rRNA bulge-helix-bulge [suggested in 76,78 ].…”
Section: Discussionmentioning
confidence: 71%
“…15f). In addition, the majority of the expected processing sites, notably at the predicted or known bulge-helix-bulge motifs 78 , were faithfully observed in P. furiosus and H. volcanii (see Supplementary Fig. 14,15).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In another study (Tang et al, 2002), it was suggested that circular 16S and 23S pre-rRNAs may be generated upon cleavage at the BHB site and subsequent ligation of exposed ends. Indeed, the presence of circular pre-rRNAs was confirmed in subsequent studies (Danan et al, 2012;Jüttner et al, 2020); however the enzyme catalyzing the reaction in vivo was unknown. More recently, using in vitro methods, it was shown that a splicing endonuclease catalyses this reaction in methanoarchaea (Qi et al, 2020).…”
Section: Introductionmentioning
confidence: 90%